Dunia Islam Abad Ke-19 M - Sitti Aisyah (Jurnal Adabiyah: Humanities and Islamic Studies, 2013)
This writing discusses about the atmosphere of ninetenth century as the view of most dramatic history of East and West. The domination of West on East brings about fundamental transformation for modernization process in Islamic world in redifining religious identity in the modern Islam context. Global penetration of the West to Islamic world caused the decline of moslem community